Volume 8: 29th Conference on Mechanical Vibration and Noise 2017
DOI: 10.1115/detc2017-68130
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Stockbridge Damper and Vibration Analysis: Equivalent Cable Stiffness

Abstract: Abstract-Aeolian vibrations are the major cause for the failure of conductor cables. Using a Stockbridge damper reduces these vibrations and increases the life span of the conductor cable. Designing an efficient Stockbridge damper that suits the conductor cable requires a robust mathematical model with minimum assumptions. However it is not easy to analytically model the complex geometry of the messenger. Therefore an equivalent stiffness must be determined so that it can be used in the analytical model. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
1
0
1
Order By: Relevance
“…The authors reported that the motion amplitude of vibration is inversely proportional to the natural frequency. Vaja et al [7] developed a mathematical model with minimum assumptions of the Stockbridge damper that suits the conductor cable. The bending stiffness of the cable and the effect of this stiffness on the natural frequencies were examined.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the motion amplitude of vibration is inversely proportional to the natural frequency. Vaja et al [7] developed a mathematical model with minimum assumptions of the Stockbridge damper that suits the conductor cable. The bending stiffness of the cable and the effect of this stiffness on the natural frequencies were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Para evitar el fenómeno de amplificación de las oscilaciones se vienen colocando amortiguadores de masas sintonizadas en un punto cercano a la grapa de anclaje [135,51].…”
Section: Figura 35: Amortiguador Stockbridgeunclassified